Direct spectroscopic evidence of energy transfer from photo-excited semiconducting polymers to single-walled carbon nanotubes. - Nish, A; Hwang, J; Doig, J; Nicholas, R (2008)
Single-walled carbon nanotubes have been efficiently dispersed in an organic solvent using the semiconducting polymers MEHPPV and PFO. It has been found that energy is transferred to the carbon nanotubes when the polymer is photo-excited across its minimum energy gap. This is shown using photoluminescence excitation mapping in the range of both the polymer's and the nanotube's optical absorbance. Possible mechanisms for the energy transfer are discussed.